(3CgOGa JOQjS GdJGQjNs - (3QHGM, CMeOs ((3HjQhJs (3QGHWI GdCSGJPI aj GdLGeYI GddHfGfjIs, 2012)
(3JJfGhd GdebGdI CgOGa JOQjS eGOI GdJGQjN(B. (3hJbSe GdebGdI GdCgOGa Edi CgOGa YGeI HYjOI GdeOi JNJU HGdYedjI GdJQHhjI ccd hJchf eHfjI Ydi GdJhLgGJ GdSjGSjI hGdGbJUGOjI hGdGLJeGYjI hGdEjOjhdhLjI dcd HdO, hCgOGa NGUI(B. (3hJHOC GdebGdI HJHjGf GdCgOGa GdYGeI dJOQjS GdJGQjN dJTed JYQja GdJdejP Ydi ghjJg(B- (3hgPG gOa HQCj GdeDda jNGa GdHYV ef GYJeGOg aj JOQjS eGOI GdJGQjN(B- (3hJOQjH GdJdGejP Ydi GdeTGQcI GdhLOGfjI(B- (3GdPj JMhd djYfj GSJYeGd hLgGJ fXQ GdfGS aj GdeGVj dTQM GdCYeGd GdJj bGehG HgG(B- (3hGdMUhd Ydi GdeYQaI GdJGQjNjI hJfejI GdehGWfI GdUGdMI, hjjfGbT GdeDda JWHjb gPG GdgOa aj dHfGf(B. (3Ke jYQV GdCgOGa GdYGeI dJOQjS GdJGQjN MSH (BThe Scottish Education Department (3h MSH (BThe Schools Council History Project (3hjSJNdU ef Gdcd CgOGaG YGeI eTJQcI(B. (3Ke jfJbd Edi GSJNdGU GdCgOGa GdNGUI dgPg GdeGOI HfaS GdWQjbI GdJj GJHYgG aj GdCgOGa GdYGeI(B. (3hjfJbd GdeDda HYO Pdc Edi JHjGf CgOGa JOQjS GdJGQjN aj GdefGgL GddHfGfjI eHJOFG HGdefGgL GdbOjeI GdehVhYI SfI (B1946 (3MjK jNdU Edi Cfg HGdQZe ef JejRgG HcKQI hJfhY GdYfGhjf GdJGQjNjI EdG CfgG JaJbQ Edi CgOGa YGeI hCNQi NGUI JHjf GdZGjGJ ef hQGA JOQjSgG(B. (3Ke jJWQb Edi GdJZjjQ GdPj WQC Ydi GdefGgL aj SfhGJ (B1968(3, (B1970(3, (B1971 (3eHjfG GdKZQGJ hfbGW GdVYa(B. (3hjNJe GdebGdI HGdJYOjd GdCNjQ SfI (B1999 (3MjK jSLd Ydjg YOI edGMXGJ jNdU HYOgG Edi Cf gPG GdefgL TgO baRI fhYjI Ydi eSJhi GdCgOGa hfbd JOQjS GdJGQjN ef MGdJg GdbOjeI GdYbjeI Edi MGdI GdJLOO GdYdej hGdCcGOjej(B.s
(3GdfhY (B: (3ebGds
Keywords: Enseignement de l'histoire Curriculum; History Education Curricula; (3JYdje GdJGQjN GdefGgLs